Enhanced corneal permeation and antimycotic activity of itraconazole against Candida albicans via a novel nanosystem vesicle - ElMeshad, Aliaa N.; Mohsen, Amira M. (Drug delivery, 2016)
The objective of this study was to investigate the potential of spanlastics as an ophthalmic delivery system to improve the corneal permeability and antimycotic activity of itraconazole (ITZ). Spanlastics containing edge activators, including Tween 20 or 80, were produced by modified ethanol injection method and exhibited a particle size of approximately 287 nm and an entrapment efficiency of more than 88%. Less than 13% ITZ was released from spanlastics over 6 h compared to 35% from conventional niosomes. Spanlastics exerted a 1.34-fold increase in the amount of ITZ permeated through excised bovine cornea after 24 h compared to conventional niosomes. Antimycotic study revealed a significant (p < 0.05) increase in the zone of inhibition of Candida albicans culture demonstrated by spanlastics compared to ITZ powder at the same concentration level (10 mg). In vivo Draize test showed no signs of acute ocular toxicity upon application of the selected spanlastic formulation to the rabbit eye. Results revealed that spanlastics loaded with itraconazole could be a potential nanosystem in ocular drug delivery systems.